Listening to patients: using verbal data in the validation of the Aberdeen Measures of Impairment, Activity Limitation and Participation Restriction (Ab-IAP) - Horwood, Jeremy (BioMed Central, 2010)
BACKGROUND: The purpose of the study was to evaluate the validity of the self-administered Aberdeen Measures of Impairment, Activity Limitation and Participation Restriction (Ab-IAP): by investigating how participants interpret and respond to questions using the cognitive interviewing technique. METHODS: Twenty patients with osteoarthritis of the knee or hip participated in a cognitive interview whilst completing the Ab-IAP. Interviews were conducted using the concurrent 'think aloud' design. All interviews were audio recorded and transcribed verbatim and analysed (i) using a standardised classification scheme to identify four types of response problems and (ii) thematically using the constant comparative technique. RESULTS: Participants used various response strategies when answering questions about impairment, activity limitations and participation restriction. Problems were judged to be present in 3.1% of participants' responses for the item Ab-IAP(. )Thematic analysis provided insight into the type and nature of problems people experienced when completing the Ab-IAP measures. The problems identified were mainly comprehension and response problems. CONCLUSIONS: Participants had minimal difficulties completing the Ab-IAP; however those difficulties identified have prompted suggestions for improving the measures. The cognitive interviews produced results that were compatible with statistical analysis of the measures.. Cognitive interviewing was beneficial for testing the validity and acceptability of new Ab-IAP measures. The results demonstrates that the Ab-IAP, in addition to being theoretically-based and having good psychometric properties, elicits appropriate responses.